Aspectos biológicos de Caligo illioneus (Cramer, 1775) (Lepidoptera: Nymphalidae: Brassolinae) em espécies de Heliconia (Heliconiaceae) - Santos, Natália Larissa da Silva (2009)
The post-embryonic development of Caligo illioneus (Cramer, 1775) (Lepidoptera, Nymphalidae, Brassolinae) feeding on leaves of Heliconia bihai (L.) L. (Heliconiaceae), in laboratory. This study involved the following aspects: determination of larval (duration the instars, in days) and pupal stadia; the sex ratio and the viability of the eggs under laboratory conditions. Eggs and larvaes of C. illioneus were collected in leaves of H. wagneriana Petersen and maintained in the laboratory to register the dates of biological events (hatching, ecdysis, death, pupation and emergence of adults), and larvae behavior. The post-embryonic period (in days, average ± standard error) was 54,58 ± 0,44. The larval period had 40,00 ± 0,43 days and this period were represented by five instars: L1= 7,88 ± 0,23; L2= 6,42 ± 0,16; L3= 5,19 ± 0,25; L4= 7,04 ± 0,19 and L5= 13,46 ± 0,28 (the active larval period was 12,46 ± 0,28 followed by an one day prepupal period). The pupal instar was 14,58 ± 0,20 and the inactive period of the post-embryonic development was 15,58 ± 0,20. Were obtained 26 adults (the sex ratio was 0,46), that represented 56,52% of the eggs viability and 76,47% of the neonates. The morphometric analysis indicates that it is possible estimate the larval development phase based on the width of cephalic capsules, considering intervals values (in mm): L1= 1,457―1,605; L2= 1,951―2,272; L3= 3,139―3,488; L4= 4,970―5,600; L5= 7,423―8,557. The biological control agents, that naturally parasitized the imatures (egg and pupae) of C. illioneus were specimens of Conura maculata (Fabricius, 1758) (Hymenoptera: Chalcididae: Chalcidini) pupae parasitoids and a singly puparium (Diptera). For one egg were recorded specimens of Eulophidae (Hymenoptera) egg parasitoids.